A paixão da fé: uma análise a partir da obra Temor e tremor de Soren Kierkegaard. - Campelo, Rosana Delane (2018)
Kierkegaard’s thinking is placed in the context of the philosophical critique of religion, which started with Hegel. Kierkegaard is opposed to the perspective of Hegel’s Philosophy of Religion, reducing Christianity to a system dominated by logic, as well as the union between religion and philosophy, where philosophical speculation justifies and explains faith in a rational manner. The problem of the relationship between reason and faith is the starting point for the defence of faith as passion. In the book Fear and Trembling, Kierkegaard analyses the essence of the Christian faith in the biblical passage of the sacrifice of Isaac, asked by God to Abraham, in Genesis 22. Faith is understood as a dimension of subjectivity and, for Kierkegaard, “subjectivity is truth”. Such truth is attained in interiority and must make sense in the individual's life. It is from this emphasis on interiority that the philosopher establishes the discussion of authenticity and its criticism of Christianity. The objective of this paper is to outline the essence of the Christian faith in Kierkegaard, the passion of faith, to deepen the reflection on the meaning of Christianity and being a Christian today – in face of the confusion and crisis of values in contemporary society, the religious mercantilism of the Christian faith, the inconsistencies of fundamentalism and religious intolerance – giving directions to the discussion of otherness and Christian faith nowadays.